Wealth transfers and the role of collateral when lifetimes are uncertain - Abdelkrim Seghir; Juan Pablo Torres-Martinez (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2006)
We develop a general equilibrium model of wealth transfers in the presence of uncertain lifetimes and default. Without introducing exogenous debt constraints, agents are allowed to make collateral-backed promises at any state of their life span.
Keywords: D52; D91; 330; Uncertain lifetimes; Collateralized Assets; Donations; Wills.; Intertemporale Entscheidung; Entscheidung unter Unsicherheit; Sterblichkeit; Allgemeines Gleichgewicht; Theorie